Synaptic Localization of α5 GABA (A) Receptors via Gephyrin Interaction Regulates Dendritic Outgrowth and Spine Maturation - Brady, Megan L. (Dev Neurobiol, 2015)
GABA(A) receptor subunit composition is a critical determinant of receptor localization and physiology, with synaptic receptors generating phasic inhibition and extrasynaptic receptors producing tonic inhibition. Extrasynaptically localized α5 GABA(A) receptors are largely responsible for tonic inhibition in hippocampal neurons. However, we show here that inhibitory synapses also contain a constant level of α5 GABA(A) receptors throughout neuronal development, as measured by its colocalization with gephyrin, the inhibitory postsynaptic scaffolding protein. Immunoprecipitation of the α5 subunit from both cultured neurons and adult rat brain coimmunoprecipitated gephyrin, confirming this interaction in vivo. Furthermore, the α5 subunit can interact with gephyrin independent of other synaptically localized alpha subunits, as shown by immunoprecipitation experiments in HEK cells. By replacing the α5 predicted gephyrin binding domain (Residues 370–385) with either the high affinity gephyrin binding domain of the α2 subunit or homologous residues from the extrasynaptic α4 subunit that does not interact with gephyrin, α5 GABA(A) receptor localization shifted into or out of the synapse, respectively. These shifts in the ratio of synaptic/extrasynaptic α5 localization disrupted dendritic outgrowth and spine maturation. In contrast to the predominant view of α5 GABA(A) receptors being extrasynaptic and modulating tonic inhibition, we identify an intimate association of the α5 subunit with gephyrin, resulting in constant synaptic levels of α5 GABA(A)R throughout circuit formation that regulates neu ronal development.